THE SURVIVAL OF A RIGHT TO DEATH OVER ANIMALS - CANEL-DEPITRE, Béatrice (MEDECINE LEGALE DROIT MEDICAL, 2025)
Euthanasia, slaughter, sacrifice, crushing, removal, killing, hunting, fishing, trapping, elimination, this terminology reveals the relationships humans have with other animals. Humans choose time of animal death according to the categories of animals and the situations. This clarification is a prerequisite to explanation of the end of animal life programmed by humans. The foundations of this right of death on animals that humans arrogate to themselves can be explained, in the light of Descartes’ theory.